Potensi Kereta Api sebagai Angkutan Barang di Provinsi Lampung - Rahayu Sulistyorini (Balitbangda Provinsi Lampung, 2015)
In terms of traffic volume, land transportation plays an important role at Lampung Province. In land transport sub-sector at Sumatera Region, road transportation still dominate, especially for the movement of the passengers and goods. Specifically for the transport of goods, trains is primary conveyance to insure transportation continuity from commodity sourcing to processing place, marketing spot, or transfer spot to airport, bus station or shipping dock. Coal is greatly potential goods that can transport at Lampung particularly and generally at Sumatera. Coal from mine site at Tanjung Enim, South Sumatera, carried to Tarahan Port by train along the 60 railway coach each series of train and each railway coach load 50 ton coal. But there are still companies that use trucks to transport coal. It makes a negative externality for the residents who live along the streets be passed by coal trucks. The negative externality that appear is the destruction of a nation road and road infrastructure, traffic jam, pollution and the number of traffic accidents caused by coal trucks. Research conducted in three mining companies, they are PT. Bukit Asam Tbk, that used train, and two other companies, PT. Sumatera Bahtera Raya dan PT. Putera Lampung, that used trucks. Data collection was conducted using survey and interview. From analysis we can take that the factors affected the company in determining transportation was location of the mine and stockpile and The company's production targets. For transport costs per tonne/km railway has the advantage has the advantage of cheaper costs for large loads and further distance but less flexible to reach certain places. So, trucks still needed for companies that less production. Special line for coal trucks need for the trucks do not pass the highway that make destruction of a nation road and traffic jam in the interest of private companies.